HYPERREALITY AND SPIRITUAL DISRUPTION: A STUDY OF TIKTOK USERS AMONG USHULUDDIN AND PHILOSOPHY STUDENTS - Mohamad Khusnial Muhtar; Fatimah Az Zahra (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2025)
TikTok is one of the social media platforms that has a significant impact on creating hyperreality among young people, including university students. Through hyperreality, students often experience spiritual disruption, even those focused on religious and philosophical studies. This article aims to reveal hyperreality and its impact on the spirituality of TikTok users among Ushuluddin and Philosophy students. The issues discussed include how TikTok is used by the students, how hyperreality manifests, and how it influences the spirituality of the students who are inherently focused on the study of Islamic thought, various religions, and spiritual traditions. The methods employed are observation and interviews with a philosophical approach. The data obtained were analyzed using Jean Baudrillard’s theory of hyperreality and Muhammad Iqbal’s concept of Insan Kamil. The findings of this article are threefold: First, students use TikTok as a medium for entertainment, business, learning, and self-expression to enjoy and enhance their quality of life based on their perspectives. Second, hyperreality manifests in how TikTok usage becomes a simulator and creates simulacra that blur essential reality. Third, the impact on spirituality is reflected when the students constantly imitate and lose their authenticity, feel insecure, distort their true image, and orient themselves towards materialism beyond their personal spiritualism.